2011
DOI: 10.1590/s0100-204x2011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad genética en cerdos criollos mexicanos con genes candidatos asociados a características productivas

Abstract: Resumen -El objetivo de este trabajo fue comparar la variabilidad, diversidad y distancias genéticas entre cerdos criollos, Pelón Mexicano (CPM) y Cuinos (CC), con Yorkshire, cuanto a los genes candidatos CAST, DECR1, HAL, HFABP4, LEP, LIPE, MCR4, MYOG, RN Gene and genotypic frequencies, heterozygosity, genetic distances and filogenetic trees between breed groups were analyzed. In the comparison among the three breeds, the allelic and genotypic frequencies were different for CAST, DECR1, HFABP4, LEP, MCR4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…2000; Zinovieva et al., 2013 ), finding it only on wild boars from the Gdańsk forests (Poland) ( Borman et al., 2016 ). In Latin America, similar studies on domestic pigs have identified this allele on a very low frequency of heterozygotes in Colombia ( Hernández, Terranova & Muñoz Flórez, 2008 ; Rodríguez, 2004 ; Sarabia et al., 2011 ). In Argentina, studies were only performed on domestic pigs, detecting presence of this detrimental allele, both in homozygote and heterozygote conditions ( Figueroa, 2020 ; Marini et al., 2012 ).…”
Section: Introductionmentioning
confidence: 81%
“…2000; Zinovieva et al., 2013 ), finding it only on wild boars from the Gdańsk forests (Poland) ( Borman et al., 2016 ). In Latin America, similar studies on domestic pigs have identified this allele on a very low frequency of heterozygotes in Colombia ( Hernández, Terranova & Muñoz Flórez, 2008 ; Rodríguez, 2004 ; Sarabia et al., 2011 ). In Argentina, studies were only performed on domestic pigs, detecting presence of this detrimental allele, both in homozygote and heterozygote conditions ( Figueroa, 2020 ; Marini et al., 2012 ).…”
Section: Introductionmentioning
confidence: 81%